The effectiveness of project-based mathematics in the first year of high school in terms of learning environment, attitudes, academic efficacy and achievement - Rijken, Paul Edward (Curtin University, 2017)
This study of first-year high-school students in South Australia involved the effectiveness of project-based mathematics among 284 students in 7 project-based and 3 comparison classes. A mixed−methods approach combined quantitative data from learning environment, attitude, academic efficacy and achievement scales with classroom observations and student and staff interviews. MANOVA revealed between-methods differences for some learning environment, attitude and achievement scales, and that the project method was differentially effective for males and females.